2021
DOI: 10.5194/tc-15-2147-2021
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric extremes caused high oceanward sea surface slope triggering the biggest calving event in more than 50 years at the Amery Ice Shelf

Abstract: Abstract. Ice shelf instability is one of the main sources of uncertainty in Antarctica's contribution to future sea level rise. Calving events play a crucial role in ice shelf weakening but remain unpredictable, and their governing processes are still poorly understood. In this study, we analyze the unexpected September 2019 calving event from the Amery Ice Shelf, the largest since 1963 and which occurred almost a decade earlier than expected, to better understand the role of the atmosphere in calving. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Amid the ongoing energy uptake of the global ocean, this trend has high inertia and will continue in the future. Indications of Antarctic land ice destabilization are steadily gaining support (e.g., Francis, Mattingly, et al., 2021), strengthening the likelihood of the significant acceleration of sea‐level rise (SLR) during the present and following centuries. This will potentially affect coastal settlements, infrastructure, agriculture and cultural heritage sites.…”
Section: Future Climatementioning
confidence: 99%
“…Amid the ongoing energy uptake of the global ocean, this trend has high inertia and will continue in the future. Indications of Antarctic land ice destabilization are steadily gaining support (e.g., Francis, Mattingly, et al., 2021), strengthening the likelihood of the significant acceleration of sea‐level rise (SLR) during the present and following centuries. This will potentially affect coastal settlements, infrastructure, agriculture and cultural heritage sites.…”
Section: Future Climatementioning
confidence: 99%
“…6.5c). There were no major calving events from the large ice shelves in 2020, unlike 2019 with the calving of iceberg D-28 from the Amery Ice Shelf (Walker et al 2021;Francis et al 2021). However, the ice front of Pine Island Ice Shelf, a rapidly thinning ice shelf in the Amundsen Sea sector (Paolo et al 2015), retreated to its most landward location observed in recent decades following a small calving event (~200 km 2 ) in February 2020 (Lhermitte et al 2020).…”
Section: State Of the Climate In 2020mentioning
confidence: 99%
“…There were no major calving events from the large ice shelves in 2020, unlike 2019 with the calving of iceberg D-28 from the Amery Ice Shelf (Walker et al 2021;Francis et al 2021). However, the ice front of Pine Island Ice Shelf, a rapidly thinning ice shelf in the Amundsen Sea sector (Paolo et al 2015), retreated to its most landward location observed in recent decades following a small calving event (~200 km 2 ) in February 2020 (Lhermitte et al 2020).…”
Section: S336mentioning
confidence: 99%